Implementation and Optimization of Two Degree of Freedom H Loop Shaping Control for Average Current Mode Control Buck Converter using Genetic Algorithm - Somyot Kaitwanidvilai; Nuttapon Phurahong; Warachart Suwan-ngam (My University, 2021)
In this paper, we focus on the implementation and optimization of two degree of freedom (2DOF) H ∞ loop shaping control for the DC-DC buck converter.The output voltage is controlled using the current control mode called the average current mode control (ACMC).The technique using the fixed structure robust controller technique, as well as genetic algorithm (GA), is applied, resulting in the reduction of the controller order and optimal parameter for the robust proportional integral (PI) controller.In this paper, the performance of the proposed controller is compared with those using the conventional 2DOF H ∞ loop shaping controller and other techniques.According to both simulation and experimental results, the robust controller designed by the proposed technique is simple, low order, and practical, yet still retains both performance and robustness.
Keywords: Mode (computer interface); Degree (music); Buck converter; Advanced DC-DC Converters